Knowledge, attitude and practices regarding family planning methods among married men in urban field practice area of Ramnagar urban health center, Belagavi- A cross sectional study - Bharat Kumar Chaudhary; A.S. Wantamutte; Jitendra Kumar Sah (Al Ameen Medical College, 2015)
Introduction: It is estimated that the world population will reach to 8 billion by 2025.About three fourths of the world population lives in the developing country. The growth rate of India is higher compared to other countries i.e. (1.8%). Therefore, family planning is the best method which can control the growth of population. Objectives: To assess the knowledge, attitude and practice of married men regarding family planning methods. Materials and Methods: A community based cross-sectional study was conducted in the urban slum area of Gangwadi with a sample of 320 married men. Pre-designed and self administered questionnaire was used to collect the required information. Percentages and chi- square test was applied for statistical analysis. Results: In this study, only (19.1%) of married men had good knowledge about family planning methods while majority of men (58.4%) had average knowledge. Others (22.5%) had poor knowledge about the same. Only (10%) married men had positive attitude towards family planning while majority (64.4%) had average attitude. 25.6% men had negative attitude towards the same. Regarding practice, (33.1%) married men did good practice, (39.1%) men practiced negatively and (27.8%) were on an average. Conclusion: Awareness about family planning method needs to be improved among less educated family.